Investigation of the Solubility of 3, 4‐Diaminofurazan (DAF) and 3, 3′‐Diamino‐4, 4′‐azoxyfurazan (DAAF) at Temperatures Between 293.15 K and 313.15 K. Issue 5 (26th January 2016) - Qiu, Lili; Li, Yuling; Wang, Zhe; Xue, Min; Xu, Zhibin; Meng, Zihui; Ma, Xiaoqin; Yi, Da; Lin, Zhihui
Abstract: The solubilities of 3, 4‐diaminofurazan (DAF) and 3, 3′‐diamino‐4, 4′‐azoxyfurazan (DAAF) were investigated in water, dichloromethane, acetonitrile, ethyl acetate, methanol, and acetone between 293.15 K and 313.15 K. The solubility was determined by high‐pressure liquid chromatography with ultraviolet detection. The solubilities of DAF and DAAF are increased with the increasing of temperature in all solvents studied. The enthalpy of solution in each solvent was calculated according to van't Hoff Equation. Abstract :